2019
DOI: 10.1002/jso.25489
|View full text |Cite
|
Sign up to set email alerts
|

Early versus late salvage abdominoperineal resection for anal squamous cell carcinoma: Is there a difference in survival?

Abstract: Background/Objectives The first‐line treatment for anal squamous cell carcinoma is Nigro protocol chemoradiotherapy. Some patients will fail curative intent chemoradiotherapy and have persistent disease while others may have an initial response followed by disease recurrence. The goal of this study is to investigate survival in anal squamous cell carcinoma patients who fail first‐line treatment. Methods The National Cancer Database (2004‐2013) was used to identify patients with anal squamous cell carcinoma. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The largest cohort to address the timing of salvage APR was collected from the National Cancer Database (NCDB) by Fields et al and included 437 patients treated between 2004 and 2013. The results yielded no significant differences in overall survival between patients who underwent salvage APR within 6 months of CRT (early) and beyond 6 months of treatment (late) [31]. Our present study corroborates this finding as an indication that APR (recurrent vs. persistent disease) did not influence survival outcomes.…”
Section: Discussionsupporting
confidence: 86%
“…The largest cohort to address the timing of salvage APR was collected from the National Cancer Database (NCDB) by Fields et al and included 437 patients treated between 2004 and 2013. The results yielded no significant differences in overall survival between patients who underwent salvage APR within 6 months of CRT (early) and beyond 6 months of treatment (late) [31]. Our present study corroborates this finding as an indication that APR (recurrent vs. persistent disease) did not influence survival outcomes.…”
Section: Discussionsupporting
confidence: 86%
“…Predictors of worse outcomes include positive lymph nodes and positive surgical margins. 94,95 Standard surveillance for cCR patients includes physical examination, digital anorectal examination, anoscopy/flexible sigmoidoscopy, and inguinal lymph node examination for the first 5 years. 51 An annual CT scan is recommended for the first 3 years of surveillance.…”
Section: Surveillance and The Role Of The Surgeonmentioning
confidence: 99%
“…93 Approximately 10%-30% of patients will have either persistent or recurrent disease, for whom abdominal perineal resection is recommended. 94,95 The 5-year OS and DFS rates after salvage abdominal perineal resection are 39%-51% and 44%-47%, respectively. Predictors of worse outcomes include positive lymph nodes and positive surgical margins.…”
Section: Treatment For Local Sccamentioning
confidence: 99%
“…after failure of chemoradiotherapy is similar. As a result, the authors concluded that patients with persistent disease should be offered surgery just as readily as those with recurrent disease [77]. Finally, preoperatory imaging should be used to assist in patient selection, to identify those patients in whom negative margins can be obtained and to determine an appropriate rescue surgery.…”
Section: Treatment Of Progressive or Recidivant Acmentioning
confidence: 99%